2006
DOI: 10.1093/nar/gkl543
|View full text |Cite
|
Sign up to set email alerts
|

Developmental activation of the lysozyme gene in chicken macrophage cells is linked to core histone acetylation at its enhancer elements

Abstract: Native chromatin IP assays were used to define changes in core histone acetylation at the lysozyme locus during developmental maturation of chicken macrophages and stimulation to high-level expression by lipo-polysaccharide. In pluripotent precursors the lysozyme gene (Lys) is inactive and there is no acetylation of core histones at the gene, its promoter or at the upstream cis-control elements. In myeloblasts, where there is a very low level of Lys expression, H4 acetylation appears at the cis-control element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
(84 reference statements)
1
16
0
1
Order By: Relevance
“…These studies indicated that acetylated H2A.Z levels within the SP-1 promoter are uniform over a wide region, Ϫ3457 to Ϫ1109, with a slight peak at Ϫ1241 and two prominent peaks at Ϫ859 and ϩ7 directly adjacent to but not overlapping the peak site of SRCAP binding. Consistent with reports of acetylated H2A.Z distribution on other genes, greatly reduced levels of acetylated H2A.Z were also observed in the coding region of the SP-1 (12,13).…”
Section: Srcap Is Present On Both Inactive and Active Promoters-tosupporting
confidence: 90%
See 4 more Smart Citations
“…These studies indicated that acetylated H2A.Z levels within the SP-1 promoter are uniform over a wide region, Ϫ3457 to Ϫ1109, with a slight peak at Ϫ1241 and two prominent peaks at Ϫ859 and ϩ7 directly adjacent to but not overlapping the peak site of SRCAP binding. Consistent with reports of acetylated H2A.Z distribution on other genes, greatly reduced levels of acetylated H2A.Z were also observed in the coding region of the SP-1 (12,13).…”
Section: Srcap Is Present On Both Inactive and Active Promoters-tosupporting
confidence: 90%
“…H2A.Z is lost following activation, suggesting a model in which the SWR-C complex is preferentially associated with inactive promoters (3)(4)(5). The recent finding that increased levels of acetylated H2A.Z occur at active promoters (7,12,13) suggests a model in which non-acetylated H2A.Z deposited at inactive promoters becomes acetylated upon activation. An alternative model is that the SWR-C complex is present at active promoters, where it catalyzes deposition of non-acetylated H2A.Z, which becomes acetylated, or that it catalyzes deposition of acetylated H2A.Z.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations